Local adaptation responses to coastal hazards in small island communities: insights from 4 Pacific nations. Issue 104 (February 2020) - Narayan, Siddharth; Esteban, Miguel; Albert, Simon; Jamero, Ma Laurice; Crichton, Richarch; Heck, Nadine; Goby, Gillian; Jupiter, Stacy
Highlights: Assessment of adaptation to coastal hazards in 43 communities in 4 Pacific nations. Key assets threatened by hazards include homes, public toilets and cultural assets. In all locations emphasis on protective adaptation that use local resources and preserve ecosystems Ecosystem-based adaptation is the most common response and seawalls are widely preferred. Social, technical capacities, local knowledge and environment preservation are key priorities. Abstract: Coastal hazards pose a serious and increasing threat to the wellbeing of coastal communities. Adaptation responses to these hazards ideally need to be embedded in the local adaptation context. However, there is little understanding of factors that shape local adaptation choices, especially in rural and remote island settings. In this paper, we compile data on adaptation responses to coastal hazards and key factors that shape adaptation across 43 towns and villages in four Pacific island nations. Local communities cite erosion as a critical coastal hazard, even more often than coastal flooding and sea level rise. We find that communities prefer protective adaptation responses that use local knowledge and resources eand protect coastal ecosystems. Our findings reveal differences in preferred versus implemented adaptation responses.Ecosystem-based adaptation is the most commonly implemented response to coastal hazards. Seawalls and other hard structures are widely preferred and perceived as effective adaptation responses but are often not implemented due to a lack of social, institutional and technical capacity. Retreat is a highly unpopular adaptation response, and difficult to implement, as coastal communities in this study indicate a strong place attachment and are deeply embedded in their social and natural environment. Our results suggest that the selection of adaptation responses might involve important trade-offs between multiple, potentially conflicting, local priorities, such as the preference for seawalls and the need to protect coastal ecosystems. Findings emphasize the importance of considering the local context when making adaptation choices and show that even when responding to the same hazard, adaptation responses can vary significantly depending on local priorities and capacities.